(3aGJMI GdYdG aj GdQO Ydi GHf YdGs - (3YHO Gddg Hf Ydj Hf eMeO Hf CHj GdbGSe GdgGOj Edj GdMbs ((3GdMeje ef HdGO CPQY ai fGMjI dMSGf (B( (3HGdjef (B) s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd Bd eMeO cGdfLhe s
(3BNQgG (B:s
(3hCf jZaQ di hdhGdOi hGdLejY GdeSedjf hGdeSdeGJ , Efg gh GdZahQ GdQMje Je HYhf Gddg JYGdi eG bUOJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDda GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds